Proceedings of the 44th International ACM SIGIR Conference on Research and Development in Information Retrieval 2021
DOI: 10.1145/3404835.3462875
|View full text |Cite
|
Sign up to set email alerts
|

Causal Intervention for Leveraging Popularity Bias in Recommendation

Abstract: Recommender system usually faces popularity bias issues: from the data perspective, items exhibit uneven (usually long-tail) distribution on the interaction frequency; from the method perspective, collaborative filtering methods are prone to amplify the bias by over-recommending popular items. It is undoubtedly critical to consider popularity bias in recommender systems, and existing work mainly eliminates the bias effect with propensity-based unbiased learning or causal embeddings. However, we argue that not … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
91
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 242 publications
(91 citation statements)
references
References 42 publications
0
91
0
Order By: Relevance
“…In recommendation scenario, however, we still focus on promoting the accuracy of preference estimation, rather than just identifying cause-effects. Existing studies also found that the non-causal associations can contribute to the prediction accuracy [44]. The observation motivates us that not all confounders (biases) need to be discarded.…”
Section: Treatment Combinationmentioning
confidence: 87%
“…In recommendation scenario, however, we still focus on promoting the accuracy of preference estimation, rather than just identifying cause-effects. Existing studies also found that the non-causal associations can contribute to the prediction accuracy [44]. The observation motivates us that not all confounders (biases) need to be discarded.…”
Section: Treatment Combinationmentioning
confidence: 87%
“…Causal graphical model [25] is a powerful tool in causal inference and has also attracted much interest in recommender systems [41].…”
Section: Causal Graphical Model and Missing Mechanismmentioning
confidence: 99%
“…Besides, they are usually learned based on observed data and are skewed due to the closed feedback loop in recommender systems, resulting in "the rich get richer" Matthew effect [11,32,35]. In particular, the observed data possibly contains many biases including position bias [2,40], item exposure bias [32,39], user self-selection bias [31,36], and popularity bias [1,41], which are likely to result in biased models and affect users' experiences. There are several benchmarked datasets for unbiased recommendation, e.g., Yahoo!R3 [22], Coat [32], MSSD [6], and MovieLens [14], etc., which have been widely used to develop and evaluate recommendation models.…”
Section: Recommendation Models and Related Datasetsmentioning
confidence: 99%
“…Causal inference has been widely used in many machine learning applications, spanning from computer vision [23,34], natural language processing [11,12,43], to information retrieval [4]. In recommendation, most works on causal inference [25] focus on debiasing various biases in user feedback, including position bias [18], clickbait issue [37], and popularity bias [45]. The most representative idea in the existing works is Inverse Propensity Scoring (IPS) [2,28,41], which first estimates the propensity score based on some assumptions, and then uses the inverse propensity score to re-weight the samples.…”
Section: Related Workmentioning
confidence: 99%